Audible Politics: meaning between 'phōné' and 'logos' - González Fonseca, Diana (Escritura e Imagen, 2019)
The concepts of phōné and logos –taken from Aristotle’s Politics– allow us to analyze the implications concerning the word, the voice and listening. These implications encourage the question: who is granted a voice and who, reason? In the book Listening, Jean-Luc Nancy explores a similar link derived from the French words entendre and entendement, both linked to both the audible and the intelligible. In order to criticize the means in which philosophy thinks epistemology and ontology, Nancy reinterprets the values of the sonorous. On one hand, he shows that epistemology has rested on the visual testimony to legitimize itself. On the other hand, he builds an ontology of meaning based on the concept of resonance. The present text links these epistemic notions with the political consequences of deferring the audible to finally position them in the emergence of an antiocular era.
Keywords: listening; Jean-Luc Nancy; politics; Aristotle; resonance; voice; reason